Steric-bulk directed polymerization of ethylene to disentangled ultra-high molecular weight polyethylene - V. Bodkhe, Dnyaneshwar; Patel, Ketan; Shaikh, Maulali H.; Kaulage, Sandeep H.; Mahajan, Digvijay; Pol, V. Harshawardhan; Chikkali, Samir H. (European Polymer Journal, 2026)
{The electron-withdrawing pentafluorophenyl phenoxy-imine-derived titanium complexes are known to produce ultrahigh molecular weight polyethylene (UHMWPE). However, cyclohexyl phenoxy-imine-derived zirconium complexes have been reported to produce low molecular weight polyethylene. The disparity between the two types of polyethylenes and the two types of catalysts can be bridged if a titanium complex bearing sterically bulky groups is made to produce UHMWPE. We report steric bulk-directed cyclohexyl phenoxy-imine titaniumcatalyzed synthesis of UHMWPE in a disentangled state. The influence of steric bulk in a phenoxy-imine-cyclohexyl ligand framework on titanium complex formation and subsequent ethylene polymerization was investigated through a combined computational and experimental approach. Density functional theory (DFT) and buried volume analyses indicated that increasing steric demand from -H to -Me to -tert-Bu substituents enhances the buried volume around the metal center, potentially favoring high molecular weight polyethylene formation. Guided by these insights, three ligands, L1-L3, were synthesized in excellent yields and fully characterized, including by single-crystal X-ray diffraction. Treatment of L1-L3 with a titanium precursor produced respective complexes, Cat.1-Cat.3, in good yields. These were characterized by NMR, IR, MS, and single-crystal X-ray diffraction. Upon activation with various co-catalysts [methyl aluminoxane (MMAO), triisobutylaluminum (TIBA), and tetrakis (pentafluoro phenyl) borate (BT)], these complexes initiated ethylene polymerizations. The catalytic activity increased from Cat.1 to Cat.2 with growing steric bulk, but decreased for the highly hindered Cat.3, likely due to restricted monomer access to the active site. Among the three, Cat.2, in combination with MMAO, showed the best performance under optimized conditions and produced ultrahigh molecular weight polyethylene (UHMWPE
Keywords: Metal catalysis; Phenoxy-imine ligand; Polyethylene; Titanium complexes; uHMWPE